Emotion Narratives on the Political Culture of Radical Right Populist Parties in Portugal and Italy - Cristiano Gianolla; Lisete Mónico; Manuel João Cruz (Politics and Governance, 2024)
The growth of radical right politics raises concerns about authoritarian and exclusionary scenarios, while populism is understood as a logic that articulates democratic demands and strengthens political engagement. There is a lack of research on the democratic views of radical right populism. Moreover, the burgeoning literature on these phenomena generally examines either the supply or demand side of politics, neglecting the narrative dimension that emerges from the two intertwining. This article aims to fill these gaps by using the heuristic of the “emotion narrative” that circulates between the supply and demand sides of radical right populist parties to examine their political culture. Assuming that populism creates social identities through the affective articulation of popular demands, focusing on the “narrative of emotions” (and not only on the narrative dimension of particular emotions) allows us to analyse how social and political objects, facts, ideas, and scenarios generate political culture. Through a mixed-methods comparative study of Portugal and Italy, this article assesses the emotion narratives of the parties Chega and Fratelli d’Italia. The dataset includes 14 semi-structured interviews with MPs and an original survey with 1,900 responses regarding political realities (on the democratic system, power structures, ethnic diversity, political history, and role of the media) and hypothetical scenarios (on authoritarianism, the rise of migration and diversity, anti-corruption, securitisation of the state, and expanded use of referendums). The emotion narratives of radical right populist political cultures engender democratic visions rooted in exclusionary identities with positive affection for centralism, authoritarianism, and securitisation of the state, as opposed to innovation and participation.